(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Professional football clubs (PFCs) have gained recognition as health promotion (HP) settings. However, HP interventions implemented in this setting are short-lived. Establishing ownership in PFCs and collaborating with local communities are crucial for sustaining HP interventions. Utilising participatory systems approaches has shown feasible in municipality and community settings yet has not been explored with PFCs as main actors. Using PFCs as the setting, the Men’s Health Programme (MHP) aims to develop implementable and sustainable HP actions targeting men who are hard to reach in two Danish communities. This study examines the adaptation and acceptability of the participatory systems approach used in the MHP. Methods: A participatory systems approach inspired by Group Model Building (GMB) was designed for PFCs and local communities. The intervention included an initial meeting and three workshops: 1) presenting local data on men’s health behaviours and selecting a health theme, 2) co-creating a causal loop diagram (CLD), and 3) co-developing and refining HP actions. Documentation included observations (n = 8), participant registration, CLDs, and interviews with club and municipality representatives (n = 6). Interview guides focused on acceptability, adaptations to the GMB process, collaboration, and implementation of the HP actions. Data were analysed using thematic analysis. Results: Thirty-one representatives participated in workshops, comprising PFCs (n = 9), municipalities (n = 6), and local stakeholders (n = 16). PFCs and municipalities chose physical activity as the health theme. Based on the CLDs developed at workshops, 21 action ideas were generated across four socio-ecological levels, resulting in implementable HP actions. Strong engagement and networking were observed during workshops. However, interviews suggested the intervention was better suited for PFCs with less experience collaborating with municipalities. Challenges included planning workshops in practice-driven environments, sparse use of CLDs in developing HP actions, and difficulties recruiting men within the target group for workshops. Conclusion: Participatory systems approaches can support HP action development with PFCs. However, contextual variation in established collaborations between PFCs and municipalities and the challenges of time-consuming GMB processes require refinement when implementing with PFCs. Later evaluations from MHP will determine if this approach can address challenges related to HP action sustainability and PFC ownership. Support/Funding Sources: Funded by Steno DK. Keywords: Health promotion, football clubs, men, participatory systems approach, community